analysis of montage work on Sbdp learning in class 4 elementary school bengkulu city state: Analisis karya montase siswa pada pembelajaran SBdP di kelas IV Sd negeri 04 Kota bengkulu - Akhmad Sobari Mukhtar Shihab -; Dwi Anggraini; Hasnawati (JURIDIKDAS, 2022)
This study aims to analyze five student montage works based on elements of fine art in class IV SD Negeri 04 Bengkulu City. This type of research is qualitative and uses document analysis methods to obtain data with specific purposes and uses. The results of the study were five student montage works. The instrument used was document analysis and the data collection technique used in this study was to look at the student montage works. The results of this study were obtained by collecting five student montage works, then the works were analyzed based on the elements of fine art, namely points, lines, planes, colors, shapes, textures, and darkness. The results of the analysis, namely the results of five student works, namely jungle forest, let's play, landscapes, let's garden, and protecting the environment are analyzed based on the elements of fine arts including dots, lines, planes, colors, shapes, textures, dark and light. Of the five works, the researcher analyzed each work based on the elements of art. The first work, namely the jungle of the work has seven elements of fine art including the elements of point, line, plane, shape, texture, color, darkness and light. The second work, namely let's play, has seven elements of art, namely point, line, plane, shape, texture, color, darkness and light. The third work is scenery, namely points, lines, planes, shapes, textures, colors, dark and light. The fourth element, let's gardening, is that there are elements of art that appear, namely points, lines, planes, shapes, textures, colors, dark and light. Furthermore, the fifth work, namely protecting the environment, contains elements of fine art consisting of points, lines, planes, shapes, textures, colors, dark and light.